Curriculum development of the teacher education program at the University of Turku - Win, Sint (My University, 2019)
Curriculum development is a complex phenomenon and understanding the dynamics of curriculum planning will help create a sound curriculum that responds to students’ needs and the society in which they live in. Moreover, teachers play a vital role in developing the curriculum in the Finnish context. Therefore, this study aims to investigate the complex processes and patterns underlying the curriculum development of the teacher education program at the University of Turku. It also examined the implementational changes that were made during the curriculum reform in 2016 and the plausible influencing factors or change drivers. Qualitative Content Analysis (QCA) was used to analyze the qualitative data which was collected by interviewing seven academics from the faculty of education at the University of Turku. The findings revealed that the curriculum development model of the teacher education program revolves around Empathy and consists of these stages Situation analysis, Ideating/Planning, Implementing the prototype and Evaluation. Thus, it was concluded that the curriculum development model in this study employs the mindset of ‘design thinking’ after comparing these two models. The results also pointed out the various problems or challenges that exist in teacher education as well as possible solutions.
Keywords: curriculum development, design thinking, teacher education curriculum